USING PERFORMANCE-BASED PEDAGOGY TO DEVELOP CRITICAL THINKING WITH SHAKESPEAREAN SONNETS IN PHILOLOGY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article highlights the effectiveness of text creation based on pictures in developing the speech skills of primary school students. Picture-based assignments help expand children's imagination, enrich their vocabulary, and foster creative thinking abilities.